The Meaning of Family Social Support For Covid-19 Survivor : A Phenomenological Study of Nomads who Affected by Covid-19: The Meaning of Family Social Support For Covid-19 Survivor : A Phenomenological Study of Nomads who Affected by Covid-19 - Syarifa Nadhrah Mustamin; Sylvianti Angraini; Syifa Salsabila; Megawati Simanjuntak; Yulina Eva Riany (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2022)
Family social support is a very valuable and significant social support in helping the process of recovering the health of a Covid-19 patient. This study aims to describe the perception of social support received by Covid-19 survivors who migrate. This study uses a qualitative approach with a phenomenological design. Participants involved in this study consisted of three participants who live in Indonesia, survivors of Covid-19, living far from family, and a minimum education level of high school. Samples were taken purposively, and the study was conducted in March 2021. This study found that two out of three participants hid the fact that they were positive for Covid-19 from their families. Therefore, the main source of social support for survivors who migrated came from their friends around them. Survivors receive various forms of social support during treatment, including instrumental support, emotional support, reward support, and social network support. This study concludes that each participant has felt sufficient social support even though they are far from their families.